2021
DOI: 10.3389/fcvm.2021.716716
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Transfer-RNA-Derived Small RNAs in Human With Rheumatic Heart Disease

Abstract: Rheumatic heart disease (RHD) remains a severe public health problem in developing countries. Atrial fibrillation (AF) is a medical complication of RHD. Although the understanding of disease pathogenesis has advanced in recent years, the key questions need to be addressed. Transfer RNA–derived small RNAs (tsRNAs) are a novel type of short non-coding RNAs with potential regulatory functions in various physiological and pathological processes. The present study used tsRNAs sequencing to investigate the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…tsRNAs have been identified as biomarkers or potential therapeutic targets in many cardiovascular diseases, including rheumatic heart disease [ 40 ], cardiac hypertrophy [ 13 ], heart failure [ 16 ], atherosclerosis [ 41 ], and aortic dissection [ 42 ]. There is evidence that tsRNAs regulate the proliferation [ 43 ] and phenotypic switching [ 44 ] of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…tsRNAs have been identified as biomarkers or potential therapeutic targets in many cardiovascular diseases, including rheumatic heart disease [ 40 ], cardiac hypertrophy [ 13 ], heart failure [ 16 ], atherosclerosis [ 41 ], and aortic dissection [ 42 ]. There is evidence that tsRNAs regulate the proliferation [ 43 ] and phenotypic switching [ 44 ] of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tRFs are involved in isoprenaline myocardial hypertrophy in Sprague-Dawley rats, perhaps specifically because tRF-5 binds to the 3′ UTR of the hypertrophy regulator TIMP3 mRNA and inhibits its expression, which leads to hypertrophy of cardiac myocytes [ 35 ]. In addition, Yang et al screened 77 tsRNAs that might be involved in rheumatic heart disease with atrial fibrillation by RNA sequencing, providing a reference for us to explore the regulatory role of tsRNA in rheumatic heart disease with atrial fibrillation [ 36 ]. tsRNA has also been studied in fulminant myocarditis [ 37 ], myocardial ischemia [ 38 ], and arteriosclerosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies have explored the role of tsRNAs in AF. 13 , 14 One study examined the tsRNA expression profiles in three pairs of AF and control heart tissues using high‐throughput sequencing. 13 Another study found that tsRNA‐5008a was highly expressed in an AF mouse model and promoted myocardial fibrosis by targeting SLC7A11.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 One study examined the tsRNA expression profiles in three pairs of AF and control heart tissues using high‐throughput sequencing. 13 Another study found that tsRNA‐5008a was highly expressed in an AF mouse model and promoted myocardial fibrosis by targeting SLC7A11. 14 Other sncRNAs, such as snoRNAs or piRNAs, have not been studied in AF.…”
Section: Introductionmentioning
confidence: 99%